Clinical utility of in-socket residual limb volume change measurement: case study results. - Sanders JE; Harrison DS; Allyn KJ; Myers TR; Sanders, Joan E; Harrison, Daniel S; Allyn, Katheryn J; Myers, Timothy R (Prosthetics & Orthotics International, 2009)
Bioimpedance analysis was used to measure conductive tissue extracellular fluid (ECF) volume changes in the residual limbs of four unilateral transtibial amputee subjects during standing and walking conditions. Results showed that all residual limbs experienced ECF volume decreases during 5 min standing intervals. During 5 min of walking immediately after a standing interval, the residual limbs of healthy subjects increased in ECF volume while those of diseased subjects, one with peripheral vascular disease and another with cardiovascular insufficiency and a high-salt intake, decreased. One subject demonstrated less absolute value ECF volume change during standing and walking at 12 months post-surgical revision compared with at six months. Presentation of bioimpedance data to patients improved compliance to practitioner recommendations and patient understanding. Results were useful towards clinical assessment, patient education, and decision-making about treatment.